Developing ADDIE-Based Animated Mathematics Videos to Enhance Vocational High School Students’ Conceptual Understanding of Circle Geometry - Aeryn Meiska Putri Bangun; Ekasatya Aldila Afriansyah; Adi Ihsan Imami (Program Studi Pendidikan Matematika, Universitas Majalengka, 2026)
The integration of digital media into mathematics education has become increasingly important for addressing students’ difficulties in understanding abstract mathematical concepts, particularly in geometry topics such as circles. However, mathematics instruction in vocational high schools is still frequently dominated by conventional teaching methods with limited use of interactive learning media. This study aimed to develop and evaluate Canva-based animated mathematics learning videos to enhance students’ conceptual understanding of circles at SMKN 1 Karawang. The research employed a Research and Development design using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The participants included 29 students in the experimental class and 15 students in the control class. Data were collected through expert validation sheets, practical questionnaires, observation, and essay-based learning outcome tests. Data analysis involved descriptive percentage analysis, the Shapiro–Wilk normality test, and the Mann–Whitney U test, all conducted in RStudio. The validation results showed that the developed media achieved an overall validity score of 87%, categorized as very valid. The practicality test obtained a score of 76%, indicating that the media was sufficiently practical for classroom use. Furthermore, the effectiveness test revealed a significant difference between the experimental and control groups (W = 357.5, p = 0.0004827 < 0.05), demonstrating that the animated learning videos improved students’ conceptual understanding of circles. The findings indicate that Canva-based animated videos can serve as valid, practical, and effective interactive learning media for supporting mathematics instruction in vocational education contexts